Climate and Competitive Status Modulate the Variation in Secondary Metabolites More in Leaves Than in Fine Roots of Betula pendula - Tullus, Arvo; Rusalepp, Linda; Lutter, Reimo; Rosenvald, Katrin; Kaasik, Ants; Rytter, Lars; Kontunen-Soppela, Sari; Oksanen, Elina (Frontiers in Plant Science, 2021)
Plant secondary metabolites have many important functions; they also determine the productivity and resilience of trees under climate change. The effects of environmental factors on secondary metabolites are much better understood in above-ground than in below-ground part of the tree. Competition is a crucial biotic stress factor, but little is known about the interaction effect of climate and competition on the secondary chemistry of trees. Moreover, competition effect is usually overlooked when analyzing the sources of variation in the secondary chemistry. Our aim was to clarify the effects of competitive status, within-crown light environment, and climate on the secondary chemistry of silver birch (Betula pendula Roth). We sampled leaves (from upper and lower crown) and fine roots from competitively dominant and suppressed B. pendula trees in plantations along a latitudinal gradient (56–67° N) in Fennoscandia, with mean annual temperature (MAT) range: −1 to 8 °C. Secondary metabolites in leaves (SML) and fine roots (SMFR) were determined with an HPLC-qTOF mass spectrometer. We found that SML content increased significantly with MAT. The effect of competitive stress on SML strengthened in colder climates (MAT < 4 °C). Competition and shade initiated a few similar responses in SML. SMFR varied less with MAT. Suppressed trees allocated relatively more resources to SML in warmer climates and to SMFR in colder ones. Our study revealed that the content and profile of secondary metabolites (mostly phenolic defence compounds and growth regulators) in leaves of B. pendula varied with climate and reflected the trees’ defence requirements against herbivory, exposure to irradiance and competitive status (resource supply). The metabolic profile of fine roots reflected, besides defence requirements, also different below-ground competition strategies in warmer and colder climates. An increase in carbon assimilation to secondary compounds can be expected at northern latitudes due to climate change.